Child's play – an unforeseen complication of surgical emphysema. (17th April 2018) - Graham, C.; Chung, M.; Feinberg, L.; O'Neill, F.; Balmer, C.
Abstract: Surgical emphysema is as an iatrogenic complication whereby air is dispersed within the tissues following an invasive procedure. It is relatively uncommon, however, it has been recognised that dental extractions and the use of air turbine drills can result in this complication. Here, we discuss a case report of a 35‐year‐old male re‐attending with extensive surgical emphysema following a seemingly uncomplicated dental extraction, caused by playing with his baby. This case was unusual because no dental air turbine drill was used during the dental extraction, and due to the innocuous patient activity that caused the emphysema. Consideration of the aetiology, prevention and recognition of surgical emphysema are discussed.